Carbon-coated titanium-doped lithium iron phosphate positive electrode material and preparation method thereof

By using carbon-coated titanium doping technology in the production process of lithium ferrous phosphate, the problems of low purity and unstable electrochemical performance caused by Fe2+ oxidation are solved, and the preparation of high-purity and high-performance lithium ferrous phosphate positive electrode materials are achieved, reducing production costs.

CN119674025APending Publication Date: 2025-03-21YUNNAN YUNTIANHUA
View PDF 0 Cites 7 Cited by

Patent Information

Application Number
CN202411897707.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

There is a problem of Fe2+ oxidation in the production process of existing lithium ferrous phosphate, resulting in low purity of the product and unstable electrochemical performance, and high industrial production costs.

Method used

The preparation method of carbon-coated titanium-doped lithium ferrous phosphate positive electrode material is adopted to provide a film-forming environment through the polymerization of dopamine hydrochloride, reduce Fe2+ oxidation, and improve the stability and electrochemical performance of the material through the embedding of the titanium source and the formation of a carbonized layer.

Benefits of technology

The purity and electrochemical properties of lithium ferrous phosphate are improved, production costs are reduced, and the rate performance and compaction density of the material are improved through carbon coating and titanium doping.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674025A_ABST
    Figure CN119674025A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium iron phosphate production, and discloses a carbon-coated titanium-doped lithium iron phosphate positive electrode material and a preparation method thereof.The preparation method comprises the following steps that 1, a ferrous solution and a phosphorus source solution are mixed in proportion, dopamine hydrochloride is added, a pH regulator is dropwise added in the stirring state, the pH of the solution is adjusted to 4.0-5.5, a reaction is conducted, a titanium source solution is added, and a reaction solution is obtained; after uniformly stirring, continuously dropwise adding a pH regulator to regulate the pH value of the solution to 5.5-6.5; the iron phosphate octahydrate coated with the titanium-embedded polydopamine is obtained; 2) calcining the titanium-embedded polydopamine-coated ferrous phosphate octahydrate in an inert gas atmosphere to obtain carbon-coated titanium-doped anhydrous ferrous phosphate; 3) mixing the carbon-coated titanium-doped anhydrous ferrous phosphate with lithium phosphate and a carbon source, ball-milling, mixing, spray-drying and calcining to obtain a carbon-coated titanium-doped lithium iron phosphate positive electrode material; the synthesis process is simple, and energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium iron phosphate production, and in particular to a carbon-coated titanium-doped lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium iron phosphate batteries have a wider range of applications in the power battery market and energy storage market due to their higher safety performance and long cycle life. The current synthesis methods of lithium iron phosphate mainly include liquid phase method and solid phase method. The main representative of the liquid phase method for producing lithium iron phosphate is Defang Nano, and the solid phase method mainly uses iron phosphate (ammonium iron phosphate, sodium iron phosphate, iron iron phosphate) as a precursor, mixed with carbon source and lithium source, and then calcined at high temperature to prepare carbon-coated lithium iron phosphate. Due to its simple process, it has developed into the mainstream process for the preparation of lithium iron phosphate. However, with the increase in market competitiveness, the production capacity of lithium iron phosphate positive electrode materials has gradually become excessive. In order to make lithium iron phosphate products competitive in the current form, in addition to reducing the production cost of materials, it is necessary to improve the quality of the products, such as improving the rate performance of the products to meet the needs of the fast charging field, or increasing the compaction density of the materials to meet the development needs of electric vehicles in terms of long battery life. In order to reduce the production cost of lithium iron phosphate, lithium iron phosphate manufacturers using the solid phase method as the process route have gradually tended to choose the lower-priced ammonium ferric phosphate as a precursor and abandon the sodium ferric phosphate. However, the lithium iron phosphate produced with ammonium ferric phosphate as a precursor often has a lower compaction density than that of sodium ferric phosphate. In the process of looking for a more cost-effective precursor, ferrous phosphate has once again become a new candidate for precursor because its synthetic raw materials are cheap and the synthesis process is simple. Using it as a precursor can match a lower-priced lithium source in the subsequent preparation process of lithium iron phosphate, and can reduce the calcination temperature during the calcination process to save energy.

[0003] However, the following problems still exist in the ferrous phosphate precursor process:

[0004] (1) The current method for synthesizing ferrous phosphate is mainly liquid phase coprecipitation. The synthesized ferrous phosphate usually contains Fe 3+ The content is high, while Fe 2+ The content of ferrous phosphate is low, usually less than 65% of the total iron content, which leads to the presence of other types of iron phosphate in the product, and the crystallinity of the product reduces the purity of the product. In order to improve the purity of ferrous phosphate, it is usually necessary to add inert gas to protect Fe during the liquid phase synthesis process. 2+ It will not be oxidized, but the cost is high for industrial production enterprises. In addition, during the drying process, if the drying temperature is too low, the drying efficiency will be reduced, and the free water in the product cannot be completely removed; if the drying temperature is too high, it will also cause Fe in the product 2+Oxidation, so inert gas protection is often required during the drying process of ferrous phosphate. These anti-oxidation measures cannot fundamentally hinder the oxidation of Fe in the preparation process of ferrous phosphate. 2+ Contact with oxygen in the air or other oxidizing environments increases the cost of synthesis.

[0005] (2) In the preparation process of lithium iron phosphate, the purity of ferrous phosphate octahydrate is difficult to guarantee, and the Fe 2+ Unstable, new impurities may be generated during the ball milling process, calcination process and other processes, resulting in low purity of the synthesized lithium iron phosphate and difficulty in stably controlling the electrochemical properties. Summary of the invention

[0006] In order to solve the problems described in the background technology, the present invention provides a carbon-coated titanium-doped lithium iron phosphate positive electrode material and a preparation method thereof.

[0007] The scheme of the present invention is:

[0008] A method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material comprises the following steps:

[0009] 1) Mixing the ferrous solution and the phosphorus source solution in proportion, adding dopamine hydrochloride, dropping a pH regulator under stirring to adjust the solution pH to 4.0-5.5, reacting for a period of time, then adding a titanium source solution, stirring evenly and continuing to drop the pH regulator to adjust the solution pH to 5.5-6.5; obtaining polydopamine-coated ferrous phosphate octahydrate with pre-embedded titanium;

[0010] 2) calcining the titanium-embedded polydopamine-coated ferrous phosphate octahydrate obtained in step 1) in an inert gas atmosphere to remove lattice water in the ferrous phosphate octahydrate, thereby obtaining carbon-coated titanium-doped anhydrous ferrous phosphate;

[0011] 3) The carbon-coated titanium-doped anhydrous ferrous phosphate obtained in step 2) is mixed with lithium phosphate and a carbon source in a certain ratio, ball-milled, spray-dried and calcined to obtain a carbon-coated titanium-doped lithium ferrous phosphate positive electrode material.

[0012] As a preferred technical solution, the Fe 2+ The concentration is 0.8 mol / L to 1.2 mol / L; the molar ratio of the iron element in the ferrous solution to the phosphorus element in the phosphorus source solution is 1 to 1.5:1.

[0013] As a preferred technical solution, the amount of dopamine hydrochloride added in step 1) is 3% to 30% of the mass of the ferrous solution.

[0014] As a preferred technical solution, the titanium source solution in step 1) is one of tetrabutyl titanate and titanium oxalate.

[0015] As a preferred technical solution, in step 1), the titanium element in the titanium source solution is 2‰ to 4‰ of the mass of the iron element in the ferrous solution.

[0016] As a preferred technical solution, the pH regulator in step 1) is an aqueous ammonia solution.

[0017] As a preferred technical solution, the calcination conditions in the step 2) are calcination at 550° C. to 600° C. for 2 to 4 hours.

[0018] As a preferred technical solution, the calcination conditions in the step 3) are calcination at 650° C. to 830° C. for 6 to 10 hours.

[0019] As a preferred technical solution, in the step 3), the ferrous phosphate and lithium phosphate are prepared according to n(Fe):n(Li)=1:1-1.04, and the amount of carbon source is 6%-10% of the mass of the ferrous phosphate.

[0020] The invention also discloses a carbon-coated titanium-doped lithium iron phosphate positive electrode material prepared by the method.

[0021] Advantages of the present invention:

[0022] 1. In this reaction, the entire iron, phosphorus, and pH regulator system is used as a buffer solution for dopamine polymerization at the ferrous phosphate precursor synthesis end, and the ferrous ions in the system are used as catalysts for dopamine polymerization, providing a better film-forming environment for the polymerization of dopamine hydrochloride; dopamine hydrochloride and its polymer polydopamine can be used as reducing agents for the entire reaction system to reduce Fe 2+ The ferrous ion content in the ferrous phosphate precursor is increased by oxidation, and the polydopamine is in situ coated on the surface of ferrous phosphate octahydrate to increase the stability of the precursor. Furthermore, the titanium source is adsorbed and pre-buried on the surface of the precursor ferrous phosphate octahydrate by utilizing the rich functional groups of polydopamine, providing a more uniform distribution of the titanium source for the titanium doping of the rear-end lithium iron phosphate and providing more abundant channels for electron transfer.

[0023] 2. Dopamine hydrochloride can be oxidatively polymerized in an oxygen environment under acidic conditions by ferrous ion catalysis, but the precipitation of ferrous phosphate is greatly affected by the pH of the solution. Therefore, the present invention should consider both the polymerization efficiency of dopamine hydrochloride and the concentration of ferrous ions and the purity of the product. When the acidity of the solution system is lower than 4, the precipitation of ferrous phosphate is incomplete and the crystal cannot grow stably. If the pH is greater than 5.5 at this stage, the nucleation and growth rate of ferrous phosphate are too fast, which will eventually lead to a wide distribution of product particle size and uneven particles, resulting in unstable electrochemical performance. In addition, when the amount of dopamine hydrochloride is certain, the polymerization rate of dopamine hydrochloride is greater than 5.5. It will also accelerate, resulting in the weakening of the polymerization reaction in the subsequent second reaction stage, which is not conducive to the stability of the reduction effect and the uniformity of coating of the dopamine hydrochloride polymerization reaction in the whole process; therefore, in the first stage of the reaction, the pH of the solution is controlled to be 4 to 5.5, which is conducive to the precipitation of ferrous phosphate and the formation of a stable crystal form; after the first stage, the pH continues to increase in the second stage, and after the pH increases, polydopamine forms a film quickly, and the crystal grows rapidly on the basis of the first stage, and the product particle size distribution is uniform; too high a pH will also affect the stability of ferrous ions, and will also introduce ammonium ions to generate miscellaneous substances such as ammonium ferrous phosphate, resulting in a decrease in product purity, therefore, the pH of the second stage is controlled to be 5.5 to 6.5.

[0024] 3. During the preparation of anhydrous ferrous phosphate, a polydopamine carbonized layer is generated synchronously, and the titanium source is converted into anatase TiO2, that is, pre-carbon and titanium doping are carried out during the precursor synthesis process, which will be beneficial to the improvement of the electronic and ionic conductivity of the back-end lithium iron phosphate.

[0025] 4. In the liquid phase co-precipitation stage, the components in the whole system complement each other, that is, the Fe content in ferrous phosphate octahydrate is increased. 2+ The content of the material is 2.5477 W, and the organic carbon source polydopamine is in situ coated on its surface, and a high-purity anhydrous ferrous phosphate precursor with pre-embedded carbon is obtained after calcination; in the preparation of lithium ferrous phosphate, ferrous phosphate obtained by pre-coating with polydopamine and carbonization is used as the precursor, lithium phosphate is used as the lithium source, and the lithium ferrous phosphate in the calcination process is secondary in situ carbon coated with an appropriate amount of carbon source, which further improves the uniformity of carbon distribution of the material, thereby improving the electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the SEM of the lithium iron phosphate positive electrode material prepared in Example 3.

[0027] Figure 2 This is the XRD of the lithium iron phosphate positive electrode material prepared in Example 3. DETAILED DESCRIPTION

[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0029] Embodiment 1:

[0030] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0031] 1) Mixing the ferrous solution and the phosphorus source solution in proportion, adding dopamine hydrochloride, dropping a pH regulator under stirring to adjust the solution pH to 4.0-5.5, reacting for a period of time, then adding a titanium source solution, stirring evenly and continuing to drop the pH regulator to adjust the solution pH to 5.5-6.5; obtaining polydopamine-coated ferrous phosphate octahydrate with pre-embedded titanium;

[0032] 2) calcining the polydopamine-coated ferrous phosphate octahydrate with pre-embedded titanium obtained in step 1) in an inert gas atmosphere to remove lattice water in the ferrous phosphate octahydrate, thereby obtaining carbon-coated titanium-doped anhydrous ferrous phosphate;

[0033] 3) mixing the carbon-coated titanium-doped anhydrous ferrous phosphate obtained in step 2) with lithium phosphate and a carbon source in a certain ratio, ball milling, spray drying and calcining to obtain a carbon-coated titanium-doped lithium ferrous phosphate positive electrode material;

[0034] In step 1), Fe 2+ The concentration is 0.8 mol / L to 1.2 mol / L; the molar ratio of the iron element in the ferrous solution to the phosphorus element in the phosphorus source solution is 1 to 1.5:1;

[0035] In step 1), the amount of dopamine hydrochloride is 3% to 30% of the mass of the ferrous solution;

[0036] In step 1), the titanium source solution is one of tetrabutyl titanate and titanium oxalate;

[0037] In step 1), the titanium element in the titanium source solution is 2‰ to 4‰ of the mass of the iron element in the ferrous solution;

[0038] In step 1), the pH adjusting agent is an aqueous ammonia solution;

[0039] In step 2), the calcination condition is calcination at 550°C to 600°C for 2 to 4 hours;

[0040] In step 3), the calcination condition is 650° C. to 830° C. for 6 to 10 hours;

[0041] In step 3), ferrous phosphate and lithium phosphate are mixed according to n(Fe):n(Li)=1:1-1.04, and the amount of carbon source is 6%-10% of the mass of ferrous phosphate.

[0042] Embodiment 2:

[0043] A lithium iron phosphate positive electrode material is prepared by the following method:

[0044] 1) Prepare 200ml Fe 2+ The concentration of ferrous sulfate solution is 0.8 mol / L. Weigh ammonium dihydrogen phosphate and dissolve it in 50 ml of water according to Fe:P=1.1:1. After it is completely dissolved, mix the two evenly.

[0045] 2) 0.5 g of dopamine hydrochloride solution was gradually added dropwise to the mixed solution under stirring. In the first reaction stage, the pH of the solution was adjusted to 4.0 and then the addition of ammonia water was stopped. After stirring for 20 minutes, 0.15 g of tetrabutyl titanate was added. After stirring evenly, ammonia water was continued to be added dropwise until the pH of the solution reached 5.5 and then the stirring reaction was continued for 30 minutes to obtain Ti-F3P2@PDA-1 octahydrate ferrous phosphate coated with polydopamine with pre-embedded titanium.

[0046] 3) calcining the Ti-F3P2@PDA-1 prepared in step 2) at 550°C for 2h under nitrogen protection to obtain carbon-coated titanium-doped anhydrous ferrous phosphate Ti-F3P2@C-1;

[0047] Weigh 15 g of Ti-F3P2@C-1 in step 3) and put it into a ball mill together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol, and mix them by ball milling. After spray drying the ball mill slurry, calcinate it at 650°C for 6 h to obtain high-performance uniformly carbon-coated titanium-doped high-performance lithium iron phosphate positive electrode material Ti-LFP@C-1.

[0048] Example 3

[0049] A lithium iron phosphate positive electrode material is prepared by the following method:

[0050] Prepare 200ml Fe 2+ The concentration of ferrous sulfate solution is 1 mol / L. Weigh ammonium dihydrogen phosphate and dissolve it in 60 ml of water according to Fe:P=1.25:1. After it is completely dissolved, mix the two evenly.

[0051] 2) 1.0 g of dopamine hydrochloride solution was gradually added dropwise to the mixed solution under stirring. In the first reaction stage, the pH of the solution was adjusted to 4.5 and then the addition of ammonia water was stopped. After stirring for 20 minutes, 0.17 g of titanium oxalate was added. After stirring evenly, ammonia water was continued to be added dropwise until the pH of the solution reached 6.0 and then the stirring reaction was continued for 30 minutes to obtain Ti-F3P2@PDA-2 with pre-embedded titanium and polydopamine-coated ferrous phosphate octahydrate.

[0052] 3) calcining the Ti-F3P2@PDA-2 in step 3) at 600° C. for 2 h under nitrogen protection to obtain carbon-coated titanium-doped anhydrous ferrous phosphate Ti-F3P2@C-2;

[0053] 4) Weigh 15 g of Ti-F3P2@C-2 prepared in step 3) and put them into a ball mill together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol, and mix them by ball milling. The ball mill slurry is spray dried and calcined at 700°C for 8 h to obtain a high-performance uniformly carbon-coated titanium-doped high-performance lithium iron phosphate positive electrode material Ti-LFP@C-2.

[0054] Example 4

[0055] A lithium iron phosphate positive electrode material is prepared by the following method:

[0056] 1) Prepare 200ml Fe 2+ For a 1.2 mol / L ferrous sulfate solution, weigh ammonium dihydrogen phosphate and dissolve it in 100 ml of water at a ratio of Fe:P=1.5:1. After it is completely dissolved, mix the two evenly.

[0057] 2) 3.0 g of dopamine hydrochloride solution was gradually added dropwise to the mixed solution under stirring. In the first reaction stage, the pH of the solution was adjusted to 5.0 and then the addition of ammonia water was stopped. After stirring for 20 minutes, 0.3 g of titanium oxalate was added. After stirring evenly, ammonia water was continued to be added dropwise until the pH of the solution reached 6.5 and then the stirring reaction was continued for 30 minutes to obtain Ti-F3P2@PDA-3 with pre-embedded titanium and polydopamine-coated ferrous phosphate octahydrate.

[0058] The Ti-F3P2@PDA-3 prepared in step 2) was calcined at 600°C for 4 h under nitrogen protection to obtain carbon-coated titanium-doped anhydrous ferrous phosphate Ti-F3P2@C-3;

[0059] 4) Weigh 15 g of Ti-F3P2@C prepared in step 3) and put them into a ball mill together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol, and mix them by ball milling. The ball mill slurry is spray dried and calcined at 830°C for 6 h to obtain a high-performance uniform carbon-coated titanium-doped high-performance lithium iron phosphate positive electrode material Ti-LFP@C-3.

[0060] Comparative Example 1

[0061] A lithium iron phosphate positive electrode material is prepared by the following method:

[0062] 1) Prepare 200ml Fe 2+ For a 1.2 mol / L ferrous sulfate solution, weigh ammonium dihydrogen phosphate and dissolve it in 100 ml of water at a ratio of Fe:P=1.5:1. After it is completely dissolved, mix the two evenly.

[0063] 2) 5.0 g of dopamine hydrochloride solution was gradually added dropwise to the mixed solution under stirring. In the first reaction stage, the pH of the solution was adjusted to 5.0 and then the addition of ammonia solution was stopped. After stirring for 20 minutes, ammonia solution was continued to be added dropwise until the pH of the solution reached 6.5 and then the stirring reaction was continued for 30 minutes to obtain polydopamine-coated ferrous phosphate octahydrate F3P2@PDA-1.

[0064] 3) calcining the F3P2@PDA-1 prepared in step 2) at 600°C for 4 h under nitrogen protection to obtain carbon-coated anhydrous ferrous phosphate F3P2@C-1;

[0065] Weigh 15 g of F3P2@C in step 3) and put it into a ball mill together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol, and mix them by ball milling. After spray drying the ball mill slurry, calcinate it at 780°C for 7 h to obtain high-performance uniform carbon-coated titanium-doped high-performance lithium iron phosphate positive electrode material LFP@C-1.

[0066] Comparative Example 2

[0067] A lithium iron phosphate positive electrode material is prepared by the following method:

[0068] 1) Prepare 200ml Fe 2+ For a 0.8 mol / L ferrous sulfate solution, weigh ammonium dihydrogen phosphate and dissolve it in 100 ml of water at a ratio of Fe:P=1.5:1. After it is completely dissolved, mix the two evenly.

[0069] 2) Gradually add ammonia solution to the mixed solution. In the first reaction stage, adjust the pH of the solution to 4.5 and then stop adding ammonia solution. After stirring for 20 minutes, add 0.15g of tetrabutyl titanate. After stirring evenly, continue to add ammonia solution until the pH of the solution reaches 6.0 and continue stirring for 30 minutes to obtain Ti-F3P2-1 pre-doped with titanium ferrous phosphate octahydrate.

[0070] 3) calcining the Ti-F3P2-1 prepared in step 2) at 550° C. for 2 h under nitrogen protection to obtain titanium-doped anhydrous ferrous phosphate Ti-F3P2-1;

[0071] 4) Weigh 15 g of Ti-F3P2-1 prepared in step 3) and put it into a ball mill together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol, and mix them by ball milling. After spray drying the ball mill slurry, calcine it at 780°C for 6 h to obtain high-performance uniformly carbon-coated titanium-doped high-performance lithium iron phosphate positive electrode material Ti-LFP-1.

[0072] Comparative Example 3

[0073] A lithium iron phosphate positive electrode material is prepared by the following method:

[0074] 1) Prepare 200ml Fe 2+ The concentration of ferrous sulfate solution is 1.2 mol / L. Weigh ammonium dihydrogen phosphate and dissolve it in 80 ml of water according to Fe:P=1.25:1. After it is completely dissolved, mix the two evenly.

[0075] 2) Gradually drop ammonia solution into the mixed solution under stirring. In the first reaction stage, adjust the pH of the solution to 4.5 and then stop adding ammonia solution. After stirring for 20 minutes, continue to drop ammonia solution until the pH of the solution reaches 6.5 and continue stirring for 30 minutes to obtain ferrous phosphate octahydrate F3P2@H2O.

[0076] 3) calcining the F3P2 in step 1) at 550° C. for 2 h under nitrogen protection to obtain anhydrous ferrous phosphate F3P2;

[0077] Weigh 15 g of Ti-F3P2@C prepared in step 3) and put them together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol into a ball mill for ball milling. The ball mill slurry is spray dried and calcined at 800° C. for 6 h to obtain lithium iron phosphate positive electrode material LFP.

[0078] Comparative Example 4

[0079] A lithium iron phosphate positive electrode material is prepared by the following method:

[0080] 1) Prepare 200ml Fe 2+ For a 1.2 mol / L ferrous sulfate solution, weigh ammonium dihydrogen phosphate and dissolve it in 100 ml of water at a ratio of Fe:P=1.5:1. After it is completely dissolved, mix the two evenly.

[0081] 2) 3.0 g of dopamine hydrochloride solution, 0.3 g of titanium oxalate and an ammonia solution were gradually added dropwise to the mixed solution of step 1) while stirring, and the solution pH reached 6.5, and the stirring reaction was continued for 30 min to obtain Ti-F3P2@PDA-3 with ferrous phosphate octahydrate coated with polydopamine and pre-embedded titanium.

[0082] 3) calcining the Ti-F3P2@PDA-3 prepared in step 1) at 600°C for 4 hours under nitrogen protection to obtain carbon-coated titanium-doped anhydrous ferrous phosphate Ti-F3P2@C-3;

[0083] Weigh 15 g of Ti-F3P2@C in step 3) and put it into a ball mill together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol, and mix them by ball milling. After spray drying the ball mill slurry, calcinate it at 830°C for 6 h to obtain high-performance uniform carbon-coated titanium-doped high-performance lithium iron phosphate positive electrode material Ti-LFP@C-3.

[0084] Comparative Example 5

[0085] A lithium iron phosphate positive electrode material is prepared by the following method:

[0086] 1) Prepare 200ml Fe 2+ For a 1.2 mol / L ferrous sulfate solution, weigh ammonium dihydrogen phosphate and dissolve it in 100 ml of water at a ratio of Fe:P=1.5:1. After it is completely dissolved, mix the two evenly.

[0087] 2) 3.0 g of dopamine hydrochloride solution was gradually added dropwise to the mixed solution under stirring. In the first reaction stage, the pH of the solution was adjusted to 3.5 and then the addition of ammonia water was stopped. After stirring for 20 minutes, 0.3 g of titanium oxalate was added. After stirring evenly, ammonia water was continued to be added dropwise until the pH of the solution reached 7 and then the stirring reaction was continued for 30 minutes to obtain Ti-F3P2@PDA-4 with pre-embedded titanium and polydopamine-coated ferrous phosphate octahydrate.

[0088] 3) calcining the Ti-F3P2@PDA-4 prepared in step 1) at 600°C for 4 hours under nitrogen protection to obtain carbon-coated titanium-doped anhydrous ferrous phosphate Ti-F3P2@C-4;

[0089] Weigh 15 g of Ti-F3P2@C in step 3) and put it into a ball mill together with 4.34 g of lithium phosphate, 0.8 g of glucose and 0.8 g of polyethylene glycol, and mix them by ball milling. After spray drying the ball mill slurry, calcinate it at 830°C for 6 h to obtain high-performance uniform carbon-coated titanium-doped high-performance lithium iron phosphate positive electrode material Ti-LFP@C-4.

[0090] Embodiment 2-4, comparative example 1-5,, prepare the ferrous ion content, the total iron content in ferrous phosphate material, the result is shown in the following table 1.

[0091] Table 1 Fe content in different embodiments and comparative examples of ferrous phosphate 2+ Table of percentage and XRD crystallinity

[0092] <![CDATA[Fe 2+ Content (%)]]> Fe content (%) <![CDATA[Fe 2+ / Fe(%)]]> XRD crystallinity (%) Example 2 25.28 33.56 75.33 83.1 Example 3 26.06 32.74 79.60 85.9 Example 4 26.42 32.65 80.92 86.8 Comparative Example 1 26.41 32.82 80.46 86.2 Comparative Example 2 20.44 32.78 62.36 74.1 Comparative Example 3 19.09 32.98 57.88 69.8 Comparative Example 4 23.03 32.7 70.40 76.6 Comparative Example 5 22.75 33.54 67.83 75.5

[0093] From the analysis of the results in Table 1, it can be seen that the in-situ synchronous polymerization of dopamine hydrochloride significantly increased the proportion of divalent iron in the ferrous phosphate precursor and the crystallinity of ferrous phosphate XRD, which means that the in-situ synchronous polymerization of dopamine hydrochloride effectively improved the purity of the ferrous phosphate product. Within a certain range of addition, as the content of dopamine hydrochloride increases, the purity of the product also increases.

[0094] The iron-process lithium iron phosphate positive electrode material LiFePO4 / C obtained in Examples 2-4 and Comparative Examples 1-5 was mixed with a conductive agent SP and a binder PVDF in a mass ratio of 90:6:4, and then the synthesized lithium iron phosphate positive electrode slurry was coated on an aluminum foil, and dried in a vacuum drying oven at 80°C for 12 h to obtain a positive electrode sheet, which was assembled into a button battery using a 2032-type button battery shell. The negative electrode was metallic lithium, the diaphragm was a Celgard2320 lithium battery diaphragm, and the button battery electrical performance testing equipment was Blue Electric.

[0095] Table 2 Electrical performance test results of batteries assembled with iron-based lithium iron phosphate cathode materials obtained in different embodiments and comparative examples

[0096]

[0097] It can be seen from Table 2 that the lithium iron phosphate synthesized by the preparation method has excellent performance in terms of both the first charge and discharge capacity display and the high rate discharge capacity; correspondingly, the lithium iron phosphate prepared by the precursor synthesized in the system without polydopamine (Comparative Example 3) has a low first discharge capacity and poor rate performance. It can be seen from Comparative Examples 1 and 2 that in the process of preparing the ferrous phosphate octahydrate precursor in this scheme, whether it is the introduction of polydopamine coating or titanium pre-doping, it is beneficial to improve the electrochemical performance of the rear-end lithium iron phosphate, but the effect is not as strong as the synergistic effect of the two co-introductions, because polydopamine and titanium source are introduced in the same period, and in the anhydrous ferrous phosphate formation stage, they are respectively in-situ carbonized and in-situ converted into TiO2, and the two are evenly distributed in the precursor, while improving the electronic conductivity and ionic conductivity of the material, thereby improving the high rate discharge performance of the material. It can be seen from Comparative Example 4 that in the process of preparing the ferrous phosphate octahydrate precursor in this scheme, a two-step reaction is adopted, which is more conducive to controlling crystal growth than the one-step reaction, and obtaining a more uniform crystal particle size, which is more conducive to the performance of electrical properties. It can be seen from Comparative Example 5 that the control of pH has a great influence on the present invention. Although dopamine hydrochloride can be polymerized under the catalysis of iron ions within a wide range of pH, the pH will also affect the oxidation of ferrous ions and the growth of ferrous phosphate crystals, which is not conducive to the preparation of high-purity and high-performance lithium iron phosphate positive electrode materials.

[0098] Figure 1 and Figure 2 The SEM and XRD patterns of the lithium iron phosphate material synthesized according to Example 3 are respectively Figure 1It can be seen that the obtained lithium iron phosphate cathode material particles are evenly distributed, and the primary particles are mostly nano-sized particles; Figure 2 The XRD diagram shows that the synthesized lithium iron phosphate has obvious characteristic peaks and no impurity peaks, and has a high degree of crystallinity.

[0099] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: 1) Mixing the ferrous solution and the phosphorus source solution in proportion, adding dopamine hydrochloride, dropping a pH regulator under stirring to adjust the solution pH to 4.0-5.5, reacting for a period of time, then adding a titanium source solution, stirring evenly and continuing to drop the pH regulator to adjust the solution pH to 5.5-6.5; obtaining polydopamine-coated ferrous phosphate octahydrate with pre-embedded titanium; 2) calcining the titanium-embedded polydopamine-coated ferrous phosphate octahydrate obtained in step 1) in an inert gas atmosphere to remove lattice water in the ferrous phosphate octahydrate, thereby obtaining carbon-coated titanium-doped anhydrous ferrous phosphate; 3) The carbon-coated titanium-doped anhydrous ferrous phosphate obtained in step 2) is mixed with lithium phosphate and a carbon source according to a ratio, ball-milled, spray-dried and calcined to obtain a carbon-coated titanium-doped lithium ferrous phosphate positive electrode material.

2. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1), Fe 2+ The concentration is 0.8 mol / L to 1.2 mol / L; the molar ratio of the iron element in the ferrous solution to the phosphorus element in the phosphorus source solution is 1 to 1.5:

1.

3. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1), the amount of dopamine hydrochloride added is 3% to 30% of the mass of the ferrous solution.

4. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1), the titanium source solution is one of tetrabutyl titanate and titanium oxalate.

5. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1), the titanium element in the titanium source solution is 2‰ to 4‰ of the mass of the iron element in the ferrous solution.

6. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1), the pH adjusting agent is an aqueous ammonia solution.

7. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: The calcination condition in the step 2) is calcination at 550° C. to 600° C. for 2 to 4 hours.

8. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: The calcination conditions in the step 3) are 650° C. to 830° C. for 6 to 10 hours.

9. The method for preparing a carbon-coated titanium-doped lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 3), the ferrous phosphate and lithium phosphate are prepared according to n(Fe):n(Li)=1:1-1.04, and the amount of carbon source is 6%-10% of the mass of the ferrous phosphate.

10. A carbon-coated titanium-doped lithium iron phosphate positive electrode material, characterized in that: The carbon-coated titanium-doped lithium iron phosphate positive electrode material is prepared by the preparation method of the lithium iron phosphate positive electrode material according to any one of claims 1 to 9.

Citation Information

Cited By

  • Lithium self-supply regenerated positive electrode material in retired lithium battery and preparation method of lithium self-supply regenerated positive electrode material

    CN120049045A

  • A positive electrode material for lithium self-supply regeneration in retired lithium batteries and a preparation method thereof

    CN120049045B

  • Rate type lithium iron phosphate positive electrode material, preparation method and battery thereof

    CN120914248A

  • A rate type lithium iron phosphate cathode material, a preparation method and a battery thereof

    CN120914248B

  • Method for preparing ferrous phosphate octahydrate from ilmenite

    CN121317668A